A case of Clival Tuberculosis and associated meningitis. (December 2021) - Flynn, William Peter; Ntuli, Yevedzo; Zhang, Henry; Tiberi, Simon
Highlights: Mycobacterium tuberculosis is infamous for its ability to mimic other pathology and manifest in unusual locations. The clivus is an extremely rare site for manifestation of MTB. A high index of suspicion and empirical approach is vital for successful management, as obtaining a definitive diagnosis of intracranial MTB may take weeks or months. Intracranial MTB can cause potentially lethal complications including meningitis, hydrocephalus and infectious vasculitis, however appropriate and timely management may lead to good outcomes. Abstract: Herein we report a 30-year-old man presenting with fevers, headaches and weight loss. On admission he was disorientated and demonstrated no focal signs of neurological deficit. Magnetic resonance imaging revealed a large area of abnormal bone marrow signal centred within the clivus with extension into the sphenoid sinus and signs of associated basal meningitis. A sphenoid sinus biopsy was performed and proved non diagnostic. The patient was treated empirically with antitubercular therapy (ATT). Lumbar puncture provided cerebrospinal fluid from which Mycobacterium tuberculosis (MTB) was isolated 35 days later. His clinical course was complicated by development of communicating hydrocephalus requiring placement of a ventriculoperitoneal shunt and addition of thalidomide. The patient was discharged following a ten-week admission with complete resolution of symptoms and remains well two years later.